(untitled) (Research, Society and Development, 2022)
Introduction: The noise can bring with itself other aggravating factors, such as toluene in occupational environment. Studies suggest that concomitant exposure to both agents may cause more severe hearing changes than only one. Aim: To investigate the impact of noise and toluene on workers’ auditory health in an industry of footwear and sports materials. Method: The study was done through audiometric data of 729 workers of a footwear and sports materials industry, who had a Hearing Loss Prevention Program (HLPP) deployed and under execution, with three groups: (1) exposed to toluene and noise, (2) exposed to noise alone and (3) non exposed. A cross-over between variables, type and time of exposure to agents and sex was performed. The study was approved by Ethical Committee of Hospital Universitário Lauro Wanderley under number 2.164.722. Results: There was no statistically significant relationship between the mean auditory thresholds and the groups studied. Among the exposed workers, there was a positive but negligible correlation between time and auditory thresholds, the latter being significantly higher in males. Conclusion: In the studied industry, there was no significant differences in hearing of workers exposed to noise alone, exposed to noise and toluene, and not exposed.